Fracture analysis of clad pipe girth welds under axial loading - Sule, Aniruddh Kiranchandra (2016)
Offshore pipelines have long been used by the oil and gas industry to transport fluids. Extraction points often being located a considerable distance off the shore, pipelines are required to be proportionally long. Due to limitations in manufacturing, transportation and assembling capabilities, these pipelines consist of shorter segments welded together. The pipelines are also required to possess adequate resistance against crack extension via tearing and unstable fracture during installation and operation. However, welds have been shown to have several defects, most notable among them being surface cracks stemming from plastic deformation occurring in pipelines. The occurring defects potentially compromise the functionality of the entire pipeline. Current methods carrying out flaw assessment, e.g. BS 7910:2005 (2005), do not take into account large plastic strains. The primary objective of this paper is to determine newer methods of conducting fracture analysis concerning pipelines subject to large plastic deformation. In this study, the evolution of Crack Tip Opening Displacement (CTOD) of a pipeline with a semi-elliptical surface crack in its weld girth is subjected to a uniaxial tensile load using three-dimensional elastic-plastic fracture finite element analysis. The effects of crack depth, ratio of semi-major axis to semi-minor axis and loading conditions are investigated. It can be concluded that up to 3% global strain, CTOD varies linearly with global strain under axial loading conditions. Upon comparing the fracture assessment results of welded pipelines using BS 7910:2005 with this study, it is deduced that BS7910:2005 is over-conservative. Therefore, for pipelines with global strains up to 3%, a CTOD estimation method is recommended.